Sexual Harassment On Teenagers: Female Students Grade Eight Of Junior High School In Surakarta - Annasofia, Jihan; Nur Prakoso, Muhammad Rizky (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Sexual harassment is something that still has many victims. Victims who do not dare to speak up and perpetrators who threaten the safetyof the victim and even the victim's life. Sexual harassment can also be categorized as a criminal act that often attacks anyone withoutseewho he is. Harassment can also occur anywhere, not only in closed places, now many are carried out in public places. Then the need forus as gen z needs to learn and understand how to deal with sexual harassment either as victims or see other people who are experienced,what help we should use, we already understand.By taking data through short questions and interviews with one of the victims. It is hopedthat readers can educate colleagues about what to do and what to do if they experience something similar. And it is hoped that this examplecase can be studied and applied so that similar incidents can be reduced over time.Keywords: sexual harassment, victim treatment, female student